A bibliometric analysis on the productivity of opioid research in Malaysia - Zin, Che Suraya; Abdullah, Nor Asma Diyana; Ramli, Noorul Atiqah; Khadir, Noorsyahiruh; Zain, Nor Shahfiza; Rosley, Nor Fatin; Shaikh Rahman Bux, Siti Halimah Bux (2019)
INTRODUCTION Opioid analgesics have been widely used for the treatment of pain. In the USA, it was reported that increase in opioid prescribing is parallel with the increase of opioid use disorders such as misuse, abuse and opioids overdose related death. Little is known about the opioid situation and its related research in Malaysia. OBJECTIVES This bibliometric study provided an overview on the productivity of opioid research in Malaysia. METHOD All original articles on opioid research in Malaysia from 2006 to 2018 were included. The articles were retrieved from databases such as Scopus, Science Direct and PubMed using search terms such as opioids, methadone, fentanyl, oxycodone and morphine. Growth of publications, number of citations journals, geographical distribution and issues addressed in the publications were analysed and presented using standard bibliometric indicators. RESULTS A total of 78 research articles on opioids published between 2006-2018 were identified. The relative growth rate of publications (RGR) during the study period was 12.24%. The most common issue studied was the methadone maintenance therapy. Most articles were published in the indexed journals (98.72%) and the predominant journal was the Drug and Alcohol Dependence journal (11.54%). Almost all articles were multi-authored (99%) and the articles on buprenorphine and naltrexone reported the highest citations of 85. CONCLUSION This study showed that the focus of opioid research in Malaysia was in the field of methadone maintenance therapy. Research evaluating opioids in pain management particularly in patients with non-cancer pain is limited and require further exploration.